Particle Flow Analysis of Mechanical Properties and Failure Behaviour in Composite Rock Strata with Holes - Chuanwei Zang; Hongmo Zhu; Miao Chen; Shuo Yang; Liu Yang; Jia Zhou; Zuoru Zhang; Yang Chen (Geofluids)
Understanding the deformation failure behavior of the composite rock strata has important implications for deep underground engineering construction. Based on the uniaxial compression laboratory test of the specimens of composite rock strata containing holes, the microscopic parameters in the particle discrete element simulation are firstly calibrated. Then, the mechanical properties and failure characteristics of the composite rock strata with holes under different confining pressures are studied. The results show that different dip angles and confining pressures have significant effects on the peak strength and elastic modulus of the specimens. Under the same confining pressure, the peak strength and elastic modulus decrease first and then increase with the increasing dip angle. As the dip angle is constant, both the peak strength and elastic modulus gradually increase with the increase in confining pressure. It shows that the first area to be damaged in composite rock strata transfers from soft rock to hard rock with the increase in dip angle. With the increase in confining pressure, the range of tensile stress concentration area decreases substantially, while the range of compressive stress concentration area changes less.